2020
DOI: 10.1089/apc.2019.0181
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Mobile Phone Interventions (SMS/IVR/Calls) to Improve Adherence and Retention to Antiretroviral Treatment in Low-and Middle-Income Countries

Abstract: The use of mobile health technologies (mHealth) to ameliorate HIV care has considerably risen in low-and middle-income countries (LMICs) since 2010. Yet, the discrepancies in the results of accompanying studies warrant an updated and systematic consolidation of all available evidence. We report a systematic review of studies testing whether text/image messages, interactive voice response reminders, or calls promote adherence and retention to antiretroviral therapy (ART) in LMICs. We systematically compiled stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 58 publications
2
56
2
1
Order By: Relevance
“…Previous literature has demonstrated efficacy of some SMS interventions in improving HIV outcomes [1,2,[21][22][23], Odeny and colleagues found that messages focused on visit attendance led to increased attendance and infant HIV testing in the first 8 weeks postpartum [24], though the effect was attenuated in a pragmatic trial [25]. Lester and colleagues found that open-ended "check-in" SMS with phone call triage of participant challenges improved viral suppression, but not retention, in adult HIV care [21,26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has demonstrated efficacy of some SMS interventions in improving HIV outcomes [1,2,[21][22][23], Odeny and colleagues found that messages focused on visit attendance led to increased attendance and infant HIV testing in the first 8 weeks postpartum [24], though the effect was attenuated in a pragmatic trial [25]. Lester and colleagues found that open-ended "check-in" SMS with phone call triage of participant challenges improved viral suppression, but not retention, in adult HIV care [21,26].…”
Section: Discussionmentioning
confidence: 99%
“…Uptake of mobile phones across the developing world has been rapid in the last decade, but it is unclear how they can be most effectively used to facilitate health service delivery. Strong evidence of a positive impact on health outcomes remains scarce and the potential for scalability questionable (Chib et al, 2015;Demena et al, 2020). Moreover, although adoption of SMS reminders seems a dated topic from a developed country perspective, basic mobile phones are still the most common appliances in poorer countries although internetenabled phones have been on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…many settings a lack of clear benefit. 21 In contrast to mobile phone interventions delivered as stand-alone strategies, the multi-feature MOCT app was intentionally embedded in a health systems integration effort for coordination between the TB Referral Hospital and the AIDS Centre through weekly meetings of institution representatives, shared access to laboratory values, medication refill data, and appointment scheduling. The significantly improved mean CD4 count and rates of viral suppression at 6 months were likely the effect of enhanced adherence in patients already on ART before enrollment as well as an increase in ART coverage for patients who were not previously prescribed ART.…”
Section: Discussionmentioning
confidence: 99%